Effects of Low-Load Blood Flow Restriction Training on Rotator Cuff Strength and Hypertrophy: Case Series - Daniel W Safford; Kshamata M Shah; Frederic Breidenbach; Philip W McClure (International Journal of Sports Physical Therapy)
# Background